What exactly is the difference between a text and a display typeface? - Zender, Mike; Bigelow, Chuck; Dyson, Mary; Lonsdale, Maria dos Santos; Larson, Kevin (Visible Language, 2017)
What exactly is a display typeface? What is it about a display typeface that makes it unsuitable for reading a lot of text? These questions were stimulated by the paper in this issue, “Legibility Implications of Expressive Display Typefaces” by Sofie Beier, Katrine Sand, and Randi Starrfelt (see preceding article).